Proceedings of the 2nd International Conference on ICT for Digital, Smart, and Sustainable Development, ICIDSSD 2020, 27-28 Feb 2021
DOI: 10.4108/eai.27-2-2020.2303221
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Comparison of C4.5, CART and C5.0 Algorithms on Heart Disease Dataset using Decision Tree Method

Abstract: Data acquisition methods can be expected for patients suffering from heart disease. The resolution of this learning was to compare a similar data mining algorithm to the calculation of heart diseaseThis research paper proposed the traditional decision tree procedure and weighted decision tree procedure. Traditional decision tree process consists of C4.5, C5.0, CART processes. The weighted decision process is established suitable weights of training cases based on naïve Bayesian theorem before trying to constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…It was found that serum creatinine and ejection fraction were the two most relevant features, and an important feature can lead to more accurate predictions than using the original dataset features in a variety of machine learning test methods. This is similar to the research by Myint & Khaung [7], which uses supervised learning in the decision tree method to classify comparisons of heart disease analysis, including C4.5, C5.0, and Cart. The results showed that the C5.0 decision tree was perfected with the greatest accuracy.…”
Section: -Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…It was found that serum creatinine and ejection fraction were the two most relevant features, and an important feature can lead to more accurate predictions than using the original dataset features in a variety of machine learning test methods. This is similar to the research by Myint & Khaung [7], which uses supervised learning in the decision tree method to classify comparisons of heart disease analysis, including C4.5, C5.0, and Cart. The results showed that the C5.0 decision tree was perfected with the greatest accuracy.…”
Section: -Introductionsupporting
confidence: 66%
“…Machine learning was one of the tools that was used to analyze a large number of heart failures, using a variety of methods, but popular methods used in predicting include supervised learning, deep learning, and ensemble. In this case, supervised learning is a method for creating a model for predicting the results of the analysis or the heart failure prognosis by learning the existing patient data to make decisions on new data to analyze [4][5][6][7]. Supervised learning was used to increase the efficiency of the prediction of heart failure; for example, Chicco & Jurman [8] applied several machine learning classifiers with feature ranking tested on heart failure datasets of 299 patients.…”
Section: -Introductionmentioning
confidence: 99%